2016
DOI: 10.3847/0004-637x/820/1/67
|View full text |Cite
|
Sign up to set email alerts
|

OPTICAL OBSERVATIONS OF THE TYPE IA SUPERNOVA SN 2011fe IN M101 FOR NEARLY 500 DAYS

Abstract: We present well-sampled optical observations of the bright Type Ia supernova (SN Ia) SN 2011fe in M101. Our data, starting from ∼16 days before maximum light and extending to ∼463 days after maximum, provide an unprecedented time series of spectra and photometry for a normal SNIa. Fitting the early-time rising light curve, we find that the luminosity evolution of SN 2011fe follows a t n law, with the index n being close to 2.0 in the VRI bands but slightly larger in the U and B bands. Combining the published … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(104 citation statements)
references
References 69 publications
(98 reference statements)
6
91
1
Order By: Relevance
“…"9 radius apertures for the U spec −, B−, V −, and R−band photometry, respectively. We note that the Zhang et al (2016) U-band observations disagree with our first two U spec epochs and the Tsvetkov et al (2013) observations. We also obtained 3 epochs of LBT/LUCI J−band imaging of SN 2011fe between 2012 May and 2013 February.…”
Section: Observationscontrasting
confidence: 51%
See 1 more Smart Citation
“…"9 radius apertures for the U spec −, B−, V −, and R−band photometry, respectively. We note that the Zhang et al (2016) U-band observations disagree with our first two U spec epochs and the Tsvetkov et al (2013) observations. We also obtained 3 epochs of LBT/LUCI J−band imaging of SN 2011fe between 2012 May and 2013 February.…”
Section: Observationscontrasting
confidence: 51%
“…The data available for SN 2011fe are unparalleled, with multi-wavelength studies in the radio (Chomiuk et al 2012;Horesh et al 2012), the far-IR with Herschel (Johansson et al 2013), the mid-IR with Spitzer (McClelland et al 2013), the IR (Matheson et al 2012), the optical (Nugent et al 2011;Smith et al 2011;Richmond & Smith 2012;Munari et al 2013;Shappee et al 2013b;Patat et al 2013;Pereira et al 2013;Tsvetkov et al 2013;Kerzendorf et al 2014;Graham et al 2015b,a;Lundqvist et al 2015;Shappee et al 2015;Zhang et al 2016;Friesen et al 2017), the UV with Swift (Nugent et al 2011;Brown et al 2012) and HST (Foley & Kirshner 2013;Mazzali et al 2014;Friesen et al 2017), X-rays with Swift (Horesh et al 2012;Margutti et al 2012) and Chandra (Margutti et al 2012), and gamma rays (Isern et al 2013). By looking for observational signatures from the companion, many of these studies have already placed constraints on SNe Ia progenitor models.…”
Section: Introductionmentioning
confidence: 99%
“…In Figure 7 we compare the B V 0 -( ) color evolution of iPTF 16abcto observations of SN 2011fe (Zhang et al 2016). For both SNe the colors have been corrected for the total inferred reddening along the line of sight.…”
Section: Blue Optical Colors Shortly After Explosionmentioning
confidence: 99%
“…In particular, as seen in Figure 4, the observed g-band normalized flux (wavelength range of which is comparable to that of the rest-frame U band after taking into account the redshift effect) of ∼ 0.12 at 15.9 days before the restframe B-band peak (or 13.5 days to the observed g-band peak) is as high as the U -band excess of iPTF 14atg (Cao et al 2015) and slightly higher than another EExSN Ia in the normal branch, SN 2017cbv (Hosseinzadeh et al 2017). The blue excess is over three times higher than the U -band normalized flux of the golden-normal SN Ia, SN 2011fe, at the same epoch (Zhang et al 2016). In redder wavelengths, e.g.…”
Section: Hsc-ssp Early-phase Sne Iamentioning
confidence: 79%
“…HSC17bmhk, SN 2017cbv, and SN 2018oh) and iPTF 14atg, a subluminous SN Ia with the most prominent early UV excess discovered so far, in blue (panel (a)) and red (panel (b)) wavelengths. A U -band and a R-band light curves of SN 2011fe (solid black lines,Zhang et al 2016) are shown in panels (a) and (b), respectively. Days since the time at the half peak luminosity in each band (t 0.5peak ) are in rest frame.…”
mentioning
confidence: 99%